2009
DOI: 10.1088/0953-4075/42/12/125301
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Josephson junction with two bosonic species

Abstract: Abstract. We study an atomic Josephson junction (AJJ) in presence of two interacting Bose-Einstein condensates (BECs) confined in a double well trap. We assume that bosons of different species interact with each other. The macroscopic wave functions of the two components obey to a system of two 3D coupled GrossPitaevskii equations (GPE). We write the Lagrangian of the system, and from this we derive a system of coupled ordinary differential equations (ODE), for which the coupled pendula represent the mechanic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…The functions φ α k (x) (α = L,R) which we consider as real functions as was done for example in [29][30][31], are singleparticle wave functions tightly localized in the αth well, while the time dependence is encoded in…”
Section: Bimodal Approximationmentioning
confidence: 99%
See 3 more Smart Citations
“…The functions φ α k (x) (α = L,R) which we consider as real functions as was done for example in [29][30][31], are singleparticle wave functions tightly localized in the αth well, while the time dependence is encoded in…”
Section: Bimodal Approximationmentioning
confidence: 99%
“…Let us note, however, that the effect of the repulsion between species has been discussed thoroughly in Refs. [25][26][27][28][29][30][31][32]47], where it was found that the conventional Josephson dynamics is crucially modified by this term, even leading to measure synchronization in some limits [48]. In particular, the interspecies interaction induces the presence of additional fixed points in the problem which are related to the repulsion between components.…”
Section: Josephson Dynamics In the Spin-orbit-coupled Double Wellmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent achievement of condensing two-species Bose atoms has spurred much interest in theoretical investigations of their stationary properties as well as dynamic properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The two species can refer to the same alkali in two different internal states, two isotopes, or two different alkali.…”
Section: Introductionmentioning
confidence: 99%